If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(v + -5) = 39 Reorder the terms: 3(-5 + v) = 39 (-5 * 3 + v * 3) = 39 (-15 + 3v) = 39 Solving -15 + 3v = 39 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 3v = 39 + 15 Combine like terms: -15 + 15 = 0 0 + 3v = 39 + 15 3v = 39 + 15 Combine like terms: 39 + 15 = 54 3v = 54 Divide each side by '3'. v = 18 Simplifying v = 18
| 6x-15/2x-5 | | 13x-7=11x+3 | | 3(v-5)=9 | | Y-17=-28 | | 12+5x=-2x+61 | | -4r+5r=r | | V-v+4v=4 | | 4/x-3.4=17 | | 4x-9=3forx | | 1/4z=1 | | 3x-4=12-10 | | 15k-14k-1=13 | | 8m+24=-3m+3 | | 25+(x-5)=90 | | 4w-2w=20 | | 9/3-4*5 | | 20m-19m=2 | | 12x+4x=12 | | 2x^3-6x^2-48x-17=0 | | g(2.5)=2(2.5)-3 | | f(x)=2x^3+3x^2-5 | | (15/4)-2 | | 8q+3q-10q=12 | | 3/2(12/1) | | 12c-8=12c+24 | | -(5/4)(3) | | kx+12=3 | | 12s+4s-8s-7s=19 | | 11=-5.3+y | | 7(6+r)=42+7r | | 6z-2z-4z+2z-z=11 | | 8r+4=29r+7 |